Apuntes a la responsabilidad civil derivada de despido incausado o fraudulento en el sistema peruano: la retórica de los punitive damages y la desnaturalización del lucro cesante - Campos García, Héctor (2019)
The peruvian Supreme Court has considered at the V Labour Plenary that the remunerations left to be received in cases of uncaused or fraudulent dismissal have a compensatory nature. This interpretation has led the notion of punitive damages to be used rhetorically and has provoced that differentiated rules are established without justification in relation to void dismissal.The article explains the reasons why the Supreme Court assumed such position and criticizes those reasons. Finally, a possible solution is presented so that the magistrates do not apply the refered interpretarion in specific cases.